Numerical Investigation of Long-Haul Coherent Optical Generalized Frequency Division Multiplexing Signal - Oussama Gharbi; Sofien Mhatli; Khalil Aissaoui; Adel Aldalbahi; Rabah Attia (IEEE Photonics Journal)
Generalized frequency division multiplexing (GFDM) is a recent physical layer scheme proposed for next-generation cellular systems. Like orthogonal frequency division multiplexing (OFDM), it is based on multicarrier modulation, but the filter shape is no longer rectangular (roll off ≠ 0) and the orthogonality between subcarriers is lost. With higher flexibility, low peak to average power ratio (PAPR) and reduced out-of-band emissions compared with OFDM, GFDM modulation is an attractive candidate for 5G application scenarios. This paper explores the performance of 10 Gb/s GFDM system over the optical link in terms of PAPR, quality factor (Q factor), and mean squared error using a third-order adaptive Volterra filter with 3 and 5 taps. The impact of linear impairments (chromatic dispersion, polarization mode dispersion), laser line width, and Mach–Zehnder non-linearity have been addressed. The results of our simulations indicate that the transmitted 10 Gb/s GFDM signal through an optical fiber can reach 930 Km and Q = 11.9 dB after 700 Km at –8 dBm of launch power using 5 taps third-order adaptive Volterra equalizer with an improvement of approximately 210 Km and 1.25 dB compared with the same equalizer with 3 taps.